2021
DOI: 10.1136/bmjgh-2021-005671
|View full text |Cite
|
Sign up to set email alerts
|

Trends and projections of caesarean section rates: global and regional estimates

Abstract: BackgroundThe caesarean section (CS) rate continues to increase across high-income, middle-income and low-income countries. We present current global and regional CS rates, trends since 1990 and projections for 2030.MethodsWe obtained nationally representative data on the CS rate from countries worldwide from 1990 to 2018. We used routine health information systems reports and population-based household surveys. Using the latest available data, we calculated current regional and subregional weighted averages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
607
6
35

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 718 publications
(660 citation statements)
references
References 20 publications
12
607
6
35
Order By: Relevance
“…The rates of cesarean sections (CS) have increased worldwide and are projected to continue to increase, with countries in sub-Saharan Africa experiencing the lowest rates. 1 In the World Health Organization's most recent statement on CS, they advised that no region should have a CS higher than 10% and that CS should only be conducted when medically necessary, as CS can result in significant and permanent complications. 2 Although the CS rate in the Democratic Republic of Congo (DRC) is within the recommended CS rate, women in developing countries experience a higher rate of complications due to CS compared to women in developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…The rates of cesarean sections (CS) have increased worldwide and are projected to continue to increase, with countries in sub-Saharan Africa experiencing the lowest rates. 1 In the World Health Organization's most recent statement on CS, they advised that no region should have a CS higher than 10% and that CS should only be conducted when medically necessary, as CS can result in significant and permanent complications. 2 Although the CS rate in the Democratic Republic of Congo (DRC) is within the recommended CS rate, women in developing countries experience a higher rate of complications due to CS compared to women in developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…The interviews took place at the participants’ preferred place, were recorded by the researcher and lasted on average about 50 minutes. The interview questions were developed by the authors (C.K., E.H.) on the basis of the relevant literature [ 1 , 7 9 , 14 ] and consisted of four main open-ended questions and clarifying questions about VBAC experience (Table 1 ). The interview approach was semi-structured in order to avoid limitations and biases towards specific themes and to open ‘gate’ to themes that the women wished to discuss during the interview.…”
Section: Methodsmentioning
confidence: 99%
“…In the 21 st century there has been a global concern over the increase in the number of caesarean sections (CSs) as these have been associated with an increased perinatal mortality and morbidity [ 1 ]. The observed increase constitutes an important public health issue, with potential negative consequences on the health of both the mother and the newborn [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Worldwide, the CS rate is projected to be 28.5% by 2030. 1,2 Ethiopia's 2019 demographic and health survey showed that only 48% of births were in a health facility. 3 The overall prevalence of caesarean section in Ethiopia among those who gave birth at the health institutions was 29.55%, ranging from 11.03% to 63.75%.…”
Section: Introductionmentioning
confidence: 99%